2010
DOI: 10.3324/haematol.2010.022848
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and outcome of autologous transplantation in rare myelomas

Abstract: BackgroundAs rare myelomas, i.e. the IgD, IgE, IgM and non-secretory forms, constitute only a small proportion of any study, relatively little is known about their prognosis in the era of peripheral stem cell transplantation. Design and MethodsWe used the European Group for Blood and Marrow Transplantation Myeloma Database to compare the outcome following autologous transplantation of over 20,000 patients with common myelomas (IgG, IgA and light chain myeloma) with the outcome of patients with rare myelomas: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 32 publications
3
30
3
1
Order By: Relevance
“…In this study, the median overall OS (37.7 months) was remarkably improved, possibly because of the use of novel agents as induction therapy, relative to the median OS (12 months) reported in our previously conducted study [11]; however, these outcomes are still shorter than those reported in studies conducted in Western countries [3, 10, 12, 13, 17, 18]. …”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In this study, the median overall OS (37.7 months) was remarkably improved, possibly because of the use of novel agents as induction therapy, relative to the median OS (12 months) reported in our previously conducted study [11]; however, these outcomes are still shorter than those reported in studies conducted in Western countries [3, 10, 12, 13, 17, 18]. …”
Section: Discussioncontrasting
confidence: 51%
“…Due to the limitations associated with retrospective analysis, several patients who were treated before 2006, for whom there was no free light chain data in the database and medical records, were evaluated using the European Group for Blood and Marrow Transplantation (EBMT) criteria for response evaluation [10]. The complete response (CR) category was defined as the presence of negative serum and urine immunofixation, the disappearance of any soft tissue plasmacytomas, and the presence of < 5% plasma cells in the bone marrow; our analysis included stringent CR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autologous SCT has been established as the first-line therapy for myeloma patients under 65 years old (5). This is the same as IgD myeloma, although the prognosis is poor compared with IgG, and IgA myelomas from the European Group for Blood and Marrow Transplantation Myeloma Database (12). In the present case, her age made her a marginal candidate for first-line autologous SCT; however, she refused a blood transfusion.…”
Section: A B C D E Fmentioning
confidence: 79%
“…In a study from the Centre for Blood and Marrow Research (CIBMTR) in 36 subjects my colleagues and I found similar outcomes to persons with IgG and IgA plasma cell myeloma [13]. However, another study in 17 subjects reported worse outcomes [14]. …”
mentioning
confidence: 99%